2016
DOI: 10.1002/aelm.201600233
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Formation of Nanofilaments in Resistive Memories via Tip‐Enhanced Electric Fields

Abstract: Resistive random access memory (ReRAM) has a great potential to be the next-generation non-volatile memory device. However, the random nucleation and growth of conductive fi laments (CFs) in ReRAM causes the low reliability in switching behaviors, leading to diffi culties in its practical application. This study demonstrates that manipulating electric fi elds in ReRAM via a structured electrode can provide the controllable formation of CFs. Ag pyramids that have a high-quality tip prepared via the template-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 44 publications
(127 reference statements)
4
91
0
Order By: Relevance
“…Conventional methods are not completely compatible with current flexible electronic technology because some toxic reductants, such as hydrazine, are used for chemical reduction methods and high temperatures are required for thermal reduction . Furthermore, these methods are usually nonlocal, and the RGO‐domains are modified homogeneously throughout the entire GO film, which is undesirable for tuning RS behaviors …”
Section: Introductionsupporting
confidence: 92%
“…Conventional methods are not completely compatible with current flexible electronic technology because some toxic reductants, such as hydrazine, are used for chemical reduction methods and high temperatures are required for thermal reduction . Furthermore, these methods are usually nonlocal, and the RGO‐domains are modified homogeneously throughout the entire GO film, which is undesirable for tuning RS behaviors …”
Section: Introductionsupporting
confidence: 92%
“…Previously, an AFM‐tip electrode is proved to have an effect of enhancing the electric field and strongly improves resistive parameters thanks to its tip structure accompanied with ultra‐small contact areas . Similarly, an Ag pyramidal electrode is designed and fabricated via an anisotropic etching method in Ag/Al 2 O 3 /Pt devices ( Figure ) . Compared to nanocrystal structures, pyramidal electrodes are much more efficient in concentrating electric field within an ultra‐confined region as well as leading to the ionization of Ag atoms (like a lightning rod).…”
Section: Device Structure Designmentioning
confidence: 99%
“…Compared to nanocrystal structures, pyramidal electrodes are much more efficient in concentrating electric field within an ultra‐confined region as well as leading to the ionization of Ag atoms (like a lightning rod). Therefore, RS will mainly occur at the tip and metallic CF is more likely to grow with smaller diameter and can be fractured easily with less CF residue, which contributes to stable switching characteristic, low SET/RESET voltage and forming‐free behavior …”
Section: Device Structure Designmentioning
confidence: 99%
See 1 more Smart Citation
“…After deposition of the top electrode (Au) and initial electric breakdown, a vertical nanogap with an RS property was generated, presenting a high HRS/LRS resistance ratio (>10 7 ), sub‐10 ns switching speed, and multistate storage ability, as shown in Figure f,g. Shin et al adopted a pyramid‐shaped Ag array as an electrode of the RS memory (Pt/Al 2 O 3 /Ag), achieving low set voltage of 0.48 V ± 0.02 V and reset voltage of 0.15 V ± 0.06 V with minimized deviations. Kim et al also reported an RS memory (TiN/TiO 2 /Cu cone/TiN) embedding a cone‐structured Cu cation source, showing improved RS properties compared to the conventional device with a planar bottom electrode.…”
Section: Inorganic Resistive Switching Memoriesmentioning
confidence: 99%